2013
DOI: 10.1136/ejhpharm-2013-000276.254
|View full text |Cite
|
Sign up to set email alerts
|

DSL-011 Efficacy and Safety of Epoetin Zeta in Dialysis Patients

Abstract: Background Anaemia in chronic kidney disease (CKD) remains one of the predictable and modifiable non-traditional cardiovascular risk factors. Epoetin zeta, which is a biosimilar product, is used in the treatment of anaemia associated with chronic kidney disease. Purpose This study was performed to evaluate the efficacy and safety of the biosimilar product epoetin zeta to maintain stable haemoglobin levels in dialysis patients. Materials and MethodsThis study was conducted in 2 dialysis centres with 33 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Bajraktar et al81 evaluated the safety of epoetin zeta in 33 dialysis patients and reported that 3% of the patients develop hypotension, in-dialyzers clotting, or thrombosis of the arteriovenous fistula. Perani et al87 examined the immunological reaction of epoetin zeta in 12 patients with CKD.…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations
“…Bajraktar et al81 evaluated the safety of epoetin zeta in 33 dialysis patients and reported that 3% of the patients develop hypotension, in-dialyzers clotting, or thrombosis of the arteriovenous fistula. Perani et al87 examined the immunological reaction of epoetin zeta in 12 patients with CKD.…”
Section: Safetymentioning
confidence: 99%
“… 79 One German postmarketing surveillance study of IV administered epoetin zeta in 322 eligible elderly (age ≥75 years) patients from 40 centers showed epoetin zeta as effective at maintaining Hb levels with no significant difference in mean dose requirements or safety concerns. 80 A study by Bajraktar et al 81 assessing interchangeability switched 33 patients in two dialysis centers from various ESAs to epoetin zeta. The Bajraktar et al study reported that epoetin zeta maintained target Hb with equivalent mean dose, no PRCA, and a safety profile in line for the study population.…”
Section: Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies reported the safety of epoetin zeta in patients with renal anemia. Of those, there are four clinical trials, 9,10,16,18 three observational studies, 14,30,31 and one post-hoc analysis based on two clinical trials. 26 Again there was no reported cases of anti-epoetin antibodies or PRCA associated with the administration of epoetin zeta in these trials.…”
Section: Discussionmentioning
confidence: 99%